A critical review of microbiome-derived metabolic functions and translational research in liver diseases - Ganesan, Raja; Thirumurugan, Durairaj; Vinayagam, Saranya; Kim, Dong Joon; Suk, Ki Tae; Iyer, Mahalaxmi; Yadav, Mukesh Kumar; HariKrishnaReddy, Dibbanti; Parkash, Jyoti; Wander, Arvinder; Vellingiri, Balachandar (Frontiers in Cellular and Infection Microbiology, 2025)
Significant changes in gut microbial composition are associated with chronic liver disease. Using preclinical models, it has been demonstrated that ethanol/alcohol-induced liver disease is transmissible through fecal microbiota transplantation (FMT). So, the survival rate of people with severe alcoholic hepatitis got better, which suggests that changes in the makeup and function of gut microbiota play a role in metabolic liver disease. The leaky intestinal barrier plays a major role in influencing metabolic-related liver disease development through the gut microbiota. As a result, viable bacteria and microbial products can be transported to the liver, causing inflammation, contributing to hepatocyte death, and causing the fibrotic response. As metabolic-related liver disease starts and gets worse, gut dysbiosis is linked to changes in the immune system, the bile acid composition, and the metabolic function of the microbiota in the gut. Metabolic-related liver disease, as well as its self-perpetuation, will be demonstrated using data from preclinical and human studies. Further, we summarize how untargeted treatment approaches affect the gut microbiota in metabolic-related liver disease, including dietary changes, probiotics, antibiotics, and FMT. It discusses how targeted therapies can improve liver disease in various areas. These approaches may improve metabolic-related liver disease treatment options.